PENGEMBANGAN PERANGKAT PEMBELAJARAN PROJECT BASED LEARNING (PBL) BERBASIS MAPLE MATAKULIAH KALKULUS LANJUT II - Eko Andy Purnomo; Abdul Rohman (Universitas Muhammadiyah Semarang, 2015)
Calculus multivariable is the advance level from Calculus I, Calculus II. the materials of it is the development of the previous calculus materials. On the observation phase in the class, 1) the mastery of calculus I, Calculus II, and advance calculus I is less optimum, 2) students have less motivation in following the learning process of advance calculus II, 3) students have not known the application of advance calculus II, 4) there is no advance calculus II materials in senior high school. The purpose of this study was to produce a valid learning instruments and to find out the effectiveness of the implementation of Project Based Learning (PBL) with maple-based. Development of the instruments in this research used a modified 4D models into 3-D (define, design, develop) based on the theory of Thiagarajan, Semmel, and Semmel. Results of the study: (1) the development of learning instruments with the learning model Project Based Learning (PBL) with maple-based is valid. (2) the Implementation of the learning model Project Based Learning (PBL) with maple-based is effective, indicated with : (a) the increasing of problem solving mastery, (b) there is influence of motivation and activity in solving problem mastery (c) the problem solving mastery with learning model Project Based Learning (PBL) with maple-based is increasing. Based on the research results, the lecturer can apply the learning model Project Based Learning (PBL) maple-based to improve the activity, motivation and problem solving skills.Keywords: Calculus multivariable, Project Based Learning (PBL), Maple